Estudo do efeito do estresse crônico sobre a função cardiovascular em ratos adolescentes e adultos - Duarte, Josiane de Oliveira (2016)
This study aimed to investigate the physiological and somatic changes evoked by chronic stress regimens in adolescent and adult rats, with a focus on cardiovascular function. Additionally, we evaluated the long-term changes induced by stress exposure during adolescence, as well as a possible vulnerability to effects of stress in adult animals exposure to chronic stress during adolescence. Male rats were exposed to repeated restraint stress (RRS) or chronic variable stress (CVS) during adolescence (28 days) and/or adulthood (60 days). Adrenal hypertrophy, thymus involution, and elevated plasma glucocorticoid were observed only in adolescent rats, whereas reduction in body weight was caused by both stress regimens in adults. CVS increased blood pressure and heart rate regardless of the age, whereas RRS increased blood pressure selectively in adults. Resting tachycardia evoked by CVS was associated with increased cardiac sympathetic tone in adults while a decreased cardiac parasympathetic activity was observed in adolescents. Changes in baroreflex function were evoked by both RRS and CVS, but this effect was age- and type-stress specific. The pressor response to systemic administration of a α1-adrenoceptor agonist was increased by both stress regimens in adolescents. Depressor responses to acetylcholine and the nitric oxide donor sodium nitroprusside were affected by RRS in both ages. Except for the circulating glucocorticoid change, all alterations observed during adolescence were reversed in adulthood. However, the RRS or CVS in adult animals subjected to the respective chronic stressor during adolescence evoked responses that was not identified in animals exposure to the stressors only in adulthood, including: CVSevoked increase in circulating corticosterone, adrenal hypertrophy, RRS-evoked increase in heart rate and cardiac sympathetic activity, reduction of intrinsic heart rate by CVS, and baroreflex changes evoked by both stressors. These findings suggest a stress vulnerability of adolescents to somatic and neuroendocrine effects regardless of stress regimen. Our results indicate an age- and stress type-specific influence in stressevoked cardiovascular/autonomic changes. Data suggest minimal consequences in adulthood of stress during adolescence, but indicate that stress experience during adolescence causes a vulnerability to neuroendocrine and cardiovascular effects of stress in adulthood.